Passive Fractional-order Proportional-Integral-Derivative control design of a Grid-connected Photovoltaic inverter for Maximum Power Point Tracking. (January 2022) - Thangam, Thomas; Muthuvel, Mr. K
Abstract: In this research, a novel "Passive Fractional-order Proportional-Integral-Derivative (PFoPID) controller" is proposed for Photovoltaic (PV) inverters by energy reshaping and Maximum Power Point Tracking (MPPT) is achieved via Perturb and Observe (P&O) method under different climatic conditions. As per the passivity concept, storage is linked with the DC-link's current and voltage, and for a PV system, the q-axis current is build-up where all variables are examined for fully utilizing the PV system's features. In this context, the residual energy reshaping takes place via the PFoPID controller, where a hybrid algorithm tuned the controlling parameters to the optimum. The novel hybrid model is named as Merged SLnO and DA Model (MSDM), which includes the ideas of both Sealion Optimization (SLnO) and Dragonfly Algorithm (DA). Eventually, the implemented scheme performance is validated by evaluating it with other existing schemes in terms of voltage and error analysis. Highlights: Photovoltaic systems have grown in popularity due to their numerous advantages Passive Fractional-order Proportional-Integral-Derivative controller is presented Maximum Power Point Tracking is attained by Perturb and Observe technique Merged Sea lion and Dragonfly Algorithm is used to tune the controller parameters Graphical abstract: Image, graphical abstract